(untitled) (Third Sector Social Economic Review, 2022)
This research was conducted to reveal the effect of social burnout levels of women living in Turkey on online hedonic buying and online compulsive buying behaviors. The questionnaire form prepared in line with the purpose of the research was applied to 415 women on a voluntary basis, as an online questionnaire and with the convenience sampling method. First of all, reliability analysis was made in the research, and the social burnout scale, online hedonic buying scale and online compulsive buying scale used in the research were found to be highly reliable. Factor analysis was performed to test the factor construct validity of the scales used in the study. As a result of the factor analysis, it was determined that the social burnout scale was collected in three different dimensions, and the scales measuring online hedonic buying behavior and online compulsive buying behavior were collected in one dimension. Regression analysis was conducted to determine the effect of social burnout levels of women living in Turkey on online hedonic buying behavior and online compulsive buying behavior. As a result of the analysis, it was concluded that the social burnout levels of women were effective on online compulsive buying behavior. Pearson correlation analysis was conducted to determine the relationship between women’s social burnout levels and online hedonic buying behaviors and online compulsive buying behaviors. As a result of the analysis, it was concluded that there is a positive and weak relationship between the burnout level of women, online hedonic buying behavior and online compulsive buying behavior.